Development and benefit evaluation of fermentation strategies for poly(malic acid) production from malt syrup by Aureobasidium melanogenum GXZ-6. (February 2019) - Zeng, Wei; Zhang, Bin; Li, Mengxuan; Ding, Su; Chen, Guiguang; Liang, Zhiqun
Highlights: Three fermentation strategies for PMA production from malt syrup were studied. High PMA titer 124.07 g/L was obtained by fed-batch fermentation. PMA yield 1.10 g/g and productivity 0.70 g/L·h in repeated-batch fermentation. PMA production cost is $ 1.716/kg by fed-batch fermentation at 2000 MT plant. This provides an economical strategy for large-scale PMA production. Abstract: Malt syrup, as a low-cost substrate without any pretreatment, was proved to be able to replace maltose for ploymalic acid (PMA) production by Aureobasidium melanogenum GXZ-6. The PMA titer of 55.53 ± 1.72 g/L was obtained by batch fermentation in a 10-L fermentor with addition of malate, citrate and sodium malonate. Then, a higher PMA titer of 124.07 ± 2.28 g/L was obtained in fed-batch fermentation, which increased by 123.43% than that from batch fermentation. Moreover, repeated-batch fermentation with three batches gave a PMA titer of 64.06 g/L on average with a higher yield of 0.81 g/g and productivity of 0.56 g/L·h. Fermentation process and economics analysis were performed by SuperPro Designer for a 2000 metric tons plant. Results showed that PMA production cost was as low as $ 1.716/kg by fed-batch fermentation, which provides an economical strategy for large-scale PMA production.